Case Report: subhepatic appendicitis complicated by hepatic abscess as the initial presentation of primary diffuse large B-cell lymphoma of the appendix: first reported case - Chen, Hao; Yu, Miao; Chang, Zhanping; Li, Yang; Fan, Lei; Shang, Dake; Zhang, Huili (Frontiers in Oncology, 2025)
Subhepatic appendicitis complicated by hepatic abscess is an uncommon clinical condition due to anatomical variations in the appendix’s position. Here, we report an unusual case of a 56-year-old male who initially presented with right abdominal pain and fever, misdiagnosed as bilateral kidney stones and urinary tract infection. Subsequent abdominal CT(Computed Tomography) scans revealed subhepatic appendicitis with a hepatic abscess located in segment VI of the liver. The patient underwent successful laparoscopic appendectomy and hepatic abscess drainage. Unexpectedly, histopathological examination of the appendix demonstrated diffuse large B-cell lymphoma (DLBCL), a rare form of primary appendiceal non-Hodgkin lymphoma. Immunohistochemistry confirmed the diagnosis, with tumor cells positive for CD20, CD79a, Bcl-6, and c-Myc, and a high Ki-67 proliferative index (>90%). This case highlights the diagnostic challenges associated with atypically positioned appendicitis and underscores the importance of pathological evaluation in detecting rare underlying malignancies.